ANALISIS PENGARUH STORE ENVIRONMENT DAN SERVICE QUALITY TERHADAP IMPLUSE BUYING - Verry Cyasmoro; Leonardo Vitaharsa (LPPM Universitas Asa Indonesia, 2020)
The study aimed to analyze the influence of store environment and service quality on impulse buying at Lotte Grosir Tangerang . The sampling technique used by purposive against 200 respondents. Data were collected by accindental technique using questionaire distributed to respondents. Data analysis used by regression with the tool of SPSS 22. The results of this study indicated that Store Environment has a positive influence on impulse buying, Service quality has a positive influence on Impluse buying. There is a significant effect of store environment and Service Quality variable effect Impluse buying at Lottte Groseir Tangerang, simultaneously